Reservation and Legal Provisions for Women in Rural Political Institutions (International Journal of Food and Nutritional Sciences, 2022)
Women empowerment means a social process in which new options are created for women through possibilities to become prosperous and developed. Women represent almost half of the society. Our society has been basically male dominated. Earlier, due to lack of any kind of independence, women's social and family status was no more than a dependent. Who needed the support of a man at every step. Although various efforts have been made for the purpose of women empowerment since independence. But in the last few years, the work of women empowerment has gained momentum. As a result of these efforts, women's self-confidence has increased.